New and Old Genes Associated with Primary and Established Responses to Cisplatin and Topotecan Treatment in Ovarian Cancer Cell Lines - Monika Świerczewska (Molecules, 2017)
Low efficiency of chemotherapy in ovarian cancer results from the development of drug resistance. Cisplatin (CIS) and topotecan (TOP) are drugs used in chemotherapy of this cancer. We analyzed the development of CIS and TOP resistance in ovarian cancer cell lines. Incubation of drug sensitive cell lines (W1 and A2780) with cytostatic drugs was used to determine the primary response to CIS and TOP. Quantitative polymerase chain reaction (Q-PCR) was performed to measure the expression levels of the genes. We observed decreased expression of the MCTP1 gene in all resistant cell lines. We observed overexpression of the S100A3 and HERC5 genes in TOP-resistant cell lines. Increased expression of the S100A3 gene was also observed in CIS-resistant A2780 sublines. Overexpression of the C4orf18 gene was observed in CIS- and TOP-resistant A2780 sublines. A short time of exposure to CIS led to increased expression of the ABCC2 gene in the W1 and A2780 cell lines and increased expression of the C4orf18 gene in the A2780 cell line. A short time of exposure to TOP led to increased expression of the S100A3 and HERC5 genes in both sensitive cell lines, increased expression of the C4orf18 gene in the A2780 cell line and downregulation of the MCTP1 gene in the W1 cell line. Our results suggest that changes in expression of the MCTP1, S100A3 and C4orf18 genes may be related to both CIS and TOP resistance. Increased expression of the HERC5 gene seems to be important only in TOP resistance.